Comedy In the Perspective of Performing Arts Management: Systematic Literature Review - Trisna Pradita Putra; Budi Irawanto; Timbul Haryono (IJCAS (International Journal of Creative and Arts Studies), 2023)
This research was conducted to map the breadth of various comedy art management research carried out in the period between 2012-2022. This research is a systematic literature review conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The primary data in this study journal articles were published in the electronic journal databases of Scopus, Proquest, Ebsco, and Portal Garuda. Based on an analysis of 115 selected articles, it was concluded that the theme of comedy management has been widely studied and produced in a variety of studies that can be classified into four main categories. The main categories in comedy management research are production management, distribution management, consumption, and human resource management. Research makes an important contribution and this is an important reference for the future development of comedy management studies.Â Komedi dalam Perspektif Manajemen Seni PertunjukanAbstrakPenelitian ini dilakukan untuk memetakan keluasan ragam penelitian manajemen seni komedi yang dilakan dalam kurun waktu antara tahun 2012-2022. Penelitian ini adalah sistematik literatur review yang dilakukan dengan metode PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses ). Data primer dalam penelitian ini adalh artikel jurnal yang dimuat dalam database jurnal elektronik Scopus, Proquest, Ebsco dan Porttal Garuda. Berdasarkan analisis terhadap 115 artikel yang terseleksi, disimpulkan bahwa tema manajemen komedi telah diteliti secara luas dan menghasilkan ragam kajian yang dapat diklasifikasikan dalam empat katagori utama. Katagori utama dalam penelitian manajemen komedi yaitu: manajemen produksi, manajemen distribusi, konsumsi dan manajemen sumber daya manusia. Penelitian memberikan kontribusi penting dan ini menjadi referensi penting bagi arah pengembangan kajian manajemen komedi di masa depan.